2014
DOI: 10.5433/1679-0359.2014v35n4p2129
|View full text |Cite
|
Sign up to set email alerts
|

Use of maltodextrin and a prebiotic in the feed of weaned piglets

Abstract: Two experiments were conducted to evaluate the effect of replacing lactose with maltodextrin and adding fructooligosaccharides (FOSs) to the feed of weaned piglets. The first experiment was conducted using a randomized block design with a 2 × 2 factorial arrangement (2 sources of carbohydrates: maltodextrin and lactose in the pre-starter feed and with or without the use of 0.3% FOS in the prestarter and starter feeds) with 7 repetitions in 3 animals. Performance and hematological parameters were evaluated. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Glucidex, derived from the partial hydrolysis of starch and with a dextrose equivalent of 17, has been selected to ameliorate the gastric-resistance of vesicles because a previous study demonstrated that maltodextrins with a dextrose equivalent lower than 20 are stable under acidic conditions 79 . Glucidex has prebiotic effect and in oral formulations inhibits gut colonization by pathogens and promote the formation of the beneficial biofilm, thus exerting a protective effect against acute and chronic gut disorders 80 , 81 . It was previously demonstrated that the combination of phospholipid vesicles with polymers (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Glucidex, derived from the partial hydrolysis of starch and with a dextrose equivalent of 17, has been selected to ameliorate the gastric-resistance of vesicles because a previous study demonstrated that maltodextrins with a dextrose equivalent lower than 20 are stable under acidic conditions 79 . Glucidex has prebiotic effect and in oral formulations inhibits gut colonization by pathogens and promote the formation of the beneficial biofilm, thus exerting a protective effect against acute and chronic gut disorders 80 , 81 . It was previously demonstrated that the combination of phospholipid vesicles with polymers (i.e.…”
Section: Discussionmentioning
confidence: 99%